Peaceful in Pesantren: The Involvement of Santri’s Peaceful Environment and Personality - Hidayat, Ade (Institut Agama Islam Negeri Imam Bonjol Padang, 2017)
The aim of this study is to identify the characteristics of peaceful personality of adolescent Santri (Islamic students) and their peaceful environment. The subjects of the study are 57 respondents taken from two classes (both male and female classes) of the 11th grade in Madrasah Aliyah (Mualimin) Pesantren Persis 19 Bentar Garut, academic year 2015-2016. Quantitative research was used where the data was analyzed descriptive and correlational statistics. The result of the study showed that average achievement of peaceful personality is considered high in the aspects of intrapersonal and interpersonal peaceful personality. The number of Santri’s perceptions on the condition of Pesantren’s (Islamic school) peaceful environment is also considered high. The factor of the environmental condition in Pesantren and home, according to the result of study, significantly influences the peaceful personality of adolescent Santri.